2013
DOI: 10.1002/mus.23934
|View full text |Cite
|
Sign up to set email alerts
|

Innervation zone locations in 43 superficial muscles: Toward a standardization of electrode positioning

Abstract: Knowledge of IZ location will increase standardization and repeatability of sEMG measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 59 publications
1
41
0
1
Order By: Relevance
“…The variability of the locations of the IZ among subjects was higher than that reported by Beretta Piccoli et al (2014) (5.6%) and Guzmán et al (2011) (8-15%). However, the variability is considered to be reasonable (Beretta Piccoli et al, 2014) and it could be attributed to differences in the experimental set-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of the locations of the IZ among subjects was higher than that reported by Beretta Piccoli et al (2014) (5.6%) and Guzmán et al (2011) (8-15%). However, the variability is considered to be reasonable (Beretta Piccoli et al, 2014) and it could be attributed to differences in the experimental set-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our experimental series, only an IZ along a register column was identified. It is known that the biceps brachii has several IZs distributed in a small area as strips (Masuda and Sadoyama, 1991) Nevertheless, the objective of this research was to describe the differences between the locations of IZ and MP, therefore, only the midline of the muscle was assessed, just as in other studies (Beretta Piccoli et al, 2014;Barbero et al, 2012). Future studies should determine whether these differences are observed in the more medial and lateral portions of the biceps brachii or not.…”
Section: Tablementioning
confidence: 99%
“…The course and distribution of the intramuscular nerve can be visualized in intact tissue without disruption of the structure. This method has been shown to be an ideal technique [8] for staining muscles of small animals and flat muscles of humans [2,3]. However, its application in large muscles of humans has rarely been reported [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Muscles like the biceps are large, have parallel fibres and usually have a well-defined IZ, but if the muscle is small or has a more complex arrangement of muscle fibres, then identifying the IZ can become more difficult. Studies investigating the distribution of IZ in the TA using HD-sEMG [54,55] and chemical analysis [56] have found that the distribution can be scattered and varies between subjects. Visually inspecting HD-sEMG recordings for propagating waveforms is often used to reveal the approximate location of an IZ [41,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the distribution of IZ in the TA using HD-sEMG [54,55] and chemical analysis [56] have found that the distribution can be scattered and varies between subjects. Visually inspecting HD-sEMG recordings for propagating waveforms is often used to reveal the approximate location of an IZ [41,54,55]. Other techniques have also been developed to automate the process and improve the estimation of the location [57][58][59].…”
Section: Discussionmentioning
confidence: 99%